Functional assessment in acute coronary syndrome: a systematic review of acute versus staged interventions - Federico Vergni; Silvia Buscarini; Leonardo Ciurlanti; Filippo Luca Gurgoglione; Francesco Pellone; Mario Luzi (REC: Interventional Cardiology (English Ed.))
ABSTRACT Introduction and objectives: Several tools have been implemented to assess the functional significance of coronary lesions. Their reliability in the management of acute coronary syndrome (ACS) might be affected by alterations in the acute phase that go beyond the affected area. Our main objective was to evaluate the reliability of invasive physiological indices for non-culprit lesions (NCL) in patients with ACS. Methods: We conducted a systematic review across ClinicalTrials.gov, Embase, Google Scholar, PubMed, and Web of Science from inception through 5 December 2024. Additionally, a citation analysis and web searches were conducted. Results: A total of 20 articles, with 4379 patients were included in the analysis. The main study design is a cohort study. The following methods were compared between acute and staged interventions: a) angiography-derived; b) hyperemic; and c) non-hyperemic indices. A significant difference in fractional flow reserve, instantaneous wave-free ratio, and quantitative flow ratio was found in one or more articles. There were no articles reporting any important changes in the Murray law-based quantitative flow ratio, resting distal-to-aortic coronary pressure ratio, or vessel fractional flow reserve. However, these indices rely on retrospective and/or limited data. All significant variations were observed in cohorts of ST-segment elevation myocardial infarction. Unlike quantitative flow ratio, the fractional flow reserve and instantaneous wave-free ratio demonstrated consistent directions of change towards lower and higher values, respectively. Prospective cohorts and randomized controlled trials including non-ST-segment elevation acute coronary syndrome did not prove the existence of significant differences between acute and follow-up fractional flow reserve. Conclusions: Physiological methods lack complete reliability for evaluating NCL during acute ST-segment elevation myocardial infarction. However, considering directions of change, fractional flow reserve is suitable for guiding the revascularization of acute positive NCL. Conversely, instantaneous wave-free ratio can be used to defer the revascularization of negative NCL. In non-ST-segment elevation acute coronary syndrome, fractional flow reserve is appropriate for assessing NCL within the acute phase.